Influence of pH on the balance between methanogenesis and iron reduction. Issue 2 (1st November 2018) - Marquart, Kyle A.; Haller, Ben R.; Paper, Janet M.; Flynn, Theodore M.; Boyanov, Maxim I.; Shodunke, Ganiyat; Gura, Colleen; Jin, Qusheng; Kirk, Matthew F.
Abstract: Methanogenesis and iron reduction play major roles in determining global fluxes of greenhouse gases. Despite their importance, environmental factors that influence their interactions are poorly known. Here, we present evidence that pH significantly influences the balance between each reaction in anoxic environments that contain ferric (oxyhydr)oxide minerals. In sediment bioreactors that contained goethite as a source of ferric iron, both iron reduction and methanogenesis occurred but the balance between them varied significantly with pH. Compared to bioreactors receiving acidic media (pH 6), electron donor oxidation was 85% lower for iron reduction and 61% higher for methanogenesis in bioreactors receiving alkaline media (pH 7.5). Thus, methanogenesis displaced iron reduction considerably at alkaline pH. Geochemistry data collected from U.S. aquifers demonstrate that a similar pattern also exists on a broad spatial scale in natural settings. In contrast, in bioreactors that were not augmented with goethite, clay minerals served as the source of ferric iron and the balance between each reaction did not vary significantly with pH. We therefore conclude that pH can regulate the relative contributions of microbial iron reduction and methanogenesis to carbon fluxes from terrestrial environments. We further propose that the availability of ferric (oxyhydr)oxide minerals influences the extent to which the balance between each reaction is sensitive to pH. The results of this study advance our understanding of environmental controls on microbial methane generation and provide a basis for using pH and the occurrence of ferric minerals to refine predictions of greenhouse gas fluxes.